Soluble Fibrin Complexes: Separation as a Function of pH and Characterization - Benabid, Y; Concord, E; Suscillon, M (Thrombosis and Haemostasis, 1977)
1. The influence of the pH on the separation of high molecular weight derivatives obtained by a limited action of thrombin on fibrinogen was studied by agarose gel chromatography. When the pH of the elution buffer was 8.5, non crosslinked associations were easily separated in two peaks eluted prior to the fibrinogen peak: one contained a dimer, the other several high polymers. At pH 6.5, only the fibrinogen peak appeared: the fibrinogen molecule proteolysed by thrombin formed no stable associations at this pH and was eluted with the intact fibrinogen molecule. In the presence of factor XIII and Ca++, numerous associations were obtained which are independant of the pH.2. The polypeptide chain composition of the different species separated at pH 8.5 was studied by SDS-polyacrylamide gel electrophoresis. This technic showed Aα, Bβ and γ chains in the fibrinogen peak, whereas in the chromatographic fractions containing the dimer four bands corresponding to Aα, α, Bβ and γ chains were found. In the peak containing the high polymers, only the presence of α, Bβ and γ chains was demonstrated.3. These experimental results concerning the effect of pH on the formation of soluble complexes showed that the presence of fibrin monomers in fibrinogen solution was not sufficient to promote any associations. The formation of such derivatives is strongly dependent on the pH of the solution. This obviously can be explained by an influence of the pH either on the ionization of polymerisation sites and the intermolecular bonds between the complex units or on the unmasking of the polymerisation sites by a hypothetical pH induced conformational change of the fibrinogen molecule.